Extend-and-pretend in the U.S. CRE market - Matteo Crosignani; Saketh Prazad (Federal Reserve Bank of New York, 2024)
We show that banks "extended-and-pretended" their impaired CRE mortgages in the post-pandemic period to avoid writing off their capital, leading to credit misallocation and a buildup of financial fragility. We detect this behavior using loan-level supervisory data on maturity extensions, bank assessment of credit risk, and realized defaults for loans to property owners and REITs. Extend-and-pretend crowds out new credit provision, leading to a 4.8-5.3 percent drop in CRE mortgage origination since 2022:Q1 and fuels the amount of CRE mortgages maturing in the near term. As of 2023:Q4, this "maturity wall" represents 27 percent of bank capital.
Keywords: G21; E51; R33; 330; commercial real estate; zombie lending; financial fragility; credit misallocation